The Little Data Book on Private Sector Development 2010 - World Bank (World Bank, 2012)
The global financial crisis has led to rising interest in private sector development and economic growth. There is strong evidence that crises can stimulate investment climate reform. A better investment climate makes economic adjustment easier and helps attract capital to create jobs and provide basic services. Well functioning finance markets and a robust private sector are critical in increasing productivity and growth and spreading equality of opportunity. The availability of cross-country data on the business environment has rapidly expanded in recent years, including data from the World Bank's doing business project and enterprise surveys. These data sources report on the scope and types of regulations that enhance, and constrain, business activity and provide information on business owners' assessments of the business environment. The data have led to new research, enabled benchmarking, and informed the reform process in many developing countries. Included in this guide are indicators on the economic and social context, the investment climate, private sector investment, finance and banking, and infrastructure. Though a pocket guide cannot include all relevant variables, the indicators that are included provide users with a general understanding of the private sector in each country. Indicators displayed in the tables are defined in the glossary, which also lists data sources.